Private patient perceptions about a public programme; what do private Indian tuberculosis patients really feel about directly observed treatment? - Udwadia Zarir F; Pinto Lancelot M (BMC, 2010)
Abstract Background India accounts for one-fifth of the global incident cases of tuberculosis(TB). The country presently has the world's largest directly observed treatment, short course (DOTS) programme, that has shown impressive results and covers almost 100% of the billion-plus Indian population. Despite such a successful programme, the majority of Indian patients with tuberculosis prefer private healthcare, although repeated audits of this sector have shown the quality to be poor. We aimed to ascertain the level of awareness and knowledge of private patients with tuberculosis attending our clinic at a tertiary private healthcare institute with regards to the DOTS programme, understanding the reasons behind their preference for private healthcare, and evaluating their perceptions and reasons for accepting or failing to accept directly observed therapy as a treatment option. Methods A structured interview schedule was administered to private patients with tuberculosis at the P.D. Hinduja Hospital and Medical Research Centre, Mumbai, India between January 2006 to November 2007. Results Only 30 of 200 patients (15%) were aware of the DOTS programme. After being explained what directly observed therapy was, 136 patients (68%) found this form of treatment unacceptable.183 patients (91.5%) preferred buying the drugs themselves to visiting a DOTS centre. 90 patients (45%) were not prepared to be observed while swallowing their TB drugs, finding it an intrusion of privacy. Conclusions Our study reveals a poor knowledge and awareness of the DOTS programme among the cohort of TB patients that we interviewed. The control of TB in India will undoubtedly benefit from more patients being attracted to and treated by the existing DOTS programmes. However, directly observed treatment, in its present form, is considered too rigid and intrusive and is unlikely to be accepted by a majority of patients seeking private healthcare. Novel strategies and more flexible options will have to be devised to ensure higher cure rates without compromising patient choice.